Copper canister shearing in spent nuclear fuel repository using Bodner–Partom model. (May 2020) - Khadivipanah, Peiman; Pintado, Xavier; Olivella, Sebastia; Vaunat, Jean
Abstract: This paper describes the implementation of the Bodner–Partom model for the analysis of copper corrosion barrier in canisters containing spent nuclear fuel. The Bonder–Partom constitutive model implemented in CODE_BRIGHT finite element code is compared with experimental results for validation and with the Stealth finite difference code for verification. Deep geological disposal is the most reliable alternative for the spent nuclear fuel storage. This disposal is based on the multiple barriers principle. Different barriers will prevent the release of the radionuclides and one of the barriers is the canister that will contain the spent fuel. The canister will be constructed mainly in cast iron for giving mechanical protection to the spent fuel with a copper shell for protecting the cast iron against corrosion. Due to the high strength of metals, the canister components will keep it inside the elastic region during the hydration of the buffer, so it has not been necessary to implement more accurate constitutive models for the simulation. The canister is considered more as a boundary condition rather than a component to be analysed when the hydration and swelling processes are assessed but in case of relative displacements between the lips of joints intersecting a deposition hole because of an earthquake induced by the increase of vertical load due to the accumulation of ice during a glaciation or any other tectonic effect, not likely in Baltic shield, the stresses in canister could be high enough for reaching plastic conditions and in this case, it is considered necessary to use more accurate constitutive models for the simulation of the canister–buffer system. Highlights: Viscoplastic equations for copper modeling were implemented in CODE_BRIGHT. Shear test mechanical analysis in full-scale and mock-up was done for 2D modelling. Sensitivity analysis of mesh for bentonite and copper has been analysed. Comparison between the mock-up scale and full-scale was performed.